The Benefits of Whatsapp as a Medium in Depositing Memorization of the Qur’an - Seprian Ilham; Deguchi Adelir; Qyoki Delr (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Media is a tool used to convey messages from a source to the message’s recipient. WhatsApp is an application that provides simple message and calls exchange services. Tahfidz Al-Quran is a person whocano memorize verses of the Quran from Al-fathihFatiha-nas. In memorizing the Quran during a pandemic, of course, you need media tools; WhatsApp can be used as a medium in depositing the memorization of the Quran with several existing features. Here the researcher conducted a study at the Islamic Boarding School Arabi Darul Yamani, Sasak Domain Pasisie; this study aims to determine the use of WhatsApp by tahfidz coaches in depositing memorization activities of students. The techniques used by researchers to collect data and in a format using observatioofion tIslamicic boarofnIslamiclsinterviewserview with tahfidz program supervisors and several students. The subjects of this study are tahfidz and santri or student coaches. The result of the short study is that teachers create Whats p groups that join students and the DZ teachers, a technique used by students to send videos into groups and photos when depositing Quran memorization. This is the easiest According According to students and te; theaters, this is the easiest thing to use.